Design, Synthesis, and Quorum Quenching Potential of Novel Catechol–Zingerone Conjugate to Find an Elixir to Tackle Pseudomonas aeruginosa Through the Trojan Horse Strategy - Mangal, Surabhi; Dua, Tamanna; Chauhan, Monika; Dhingra, Neelima; Chhibber, Sanjay; Singh, Vasundhara; Harjai, Kusum (Frontiers in Chemistry, 2022)
To address the issue of multi drug resistance in Pseudomonas aeruginosa, a novel catechol-zingerone conjugate (1) linked via a non hydrolyzable 1,2,3- triazole linker, was synthesized and subjected to biological evaluation based on the Trojan horse strategy. To enhance the efficacy, catechol, a xenosiderophore, utilized by P. aeruginosa for iron assimilation, and the dietary phytochemical Zingerone, known for its anti virulent activity against Pseudomonas aeruginosa, was exploited in the present study. Theoretical validation of conjugate (1) was conducted by in silico molecular docking analysis to determine the interaction with outer membrane transport receptor PirA as well as quorum sensing signal receptors. Nine fold binding affinity of Conjugate (1) towards PirA (5FP2) in comparison to its natural ligand catechol with D-score -1.13Å authenticated the designed Trojan horse drug. Conjugate (1) showed stronger anti virulent activity than zingerone, hence exhibited a promising antibiofilm efficacy as assessed by crystal violet assay and visualized by FESEM towards P. aeruginosa. Encouraging results against P. aeruginosa in terms of quorum sensing regulated virulence factors, motility phenotypes and biofilm formation with no cell cytotoxicity could help to open hitherto unexplored possibilities of establishing Trojan horse drugs as a successful approach against multi drug resistance in P. aeruginosa.